Analisis Intention Mahasiswa Memilih Program Studi Akuntansi Menggunakan Theory of Plan Behavioral - Christopher Ryan Julian; Nathania Nathania; Golrida Karyawati P; Siti Farhana (Studi Akuntansi dan Keuangan Indonesia, 2020)
This study aims to analyze student intentions in choosing an accounting major using Theory of Plan Behavior (TPB). TPB is used to determine whether the decision to take education in an accounting study program is a momentary decision or is the result of the behavior of the plan. This study is important given the issues regarding the industrial revolution 4.0. currently it is feared that it threatens the existence of accounting study programs in Indonesia. This study conducted a survey of 10 college majoring in accounting students in Greater Jakarta in Indonesia. Regression models are used to analyze the influence of attitudes, subjective norms and behavioral control in determining intentions to choose an accounting major. The results showed that the decision to choose an accounting major was based on intentions generated from the plan behaviour. The analysis also found that students with a science education background also chose accounting majors. The results of this study are expected to provide confidence to institutions that hold accounting study programs in carrying out their programs and adapt to changes caused by the industrial revolution 4.0. Keywords: Attitude, behavioral control, intention, Theory of Planned Behaviour (TPB), subjective norm https://doi.org/10.21632/saki.2.2.277-298